Financial Socialization, Social Comparison, and Financial Behavior: The Mediating Role of Self-Efficacy - Sri Ayu Devista; Ahmad Wira; Romi Iskandar (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
Financial management behavior is essential for the sustainability of Micro, Small, and Medium Enterprises (MSMEs), yet many MSME actors still struggle to manage business finances effectively. While prior research has examined financial socialization and social comparison orientation as external drivers of financial behavior, little is known about how these factors operate through financial self-efficacy as a psychological mechanism, particularly among MSME actors in emerging urban economies such as Padang City, Indonesia. This study addresses this gap by testing financial self-efficacy as a mediator between financial socialization, social comparison orientation, and financial management behavior, using SEM-PLS on survey data from 100 MSME actors selected through purposive sampling. The findings show that financial socialization, not social comparison, is the determinant that meaningfully shapes financial management behavior, both directly and through financial self-efficacy. This distinction represents the study's key contribution: it demonstrates that internalized confidence built through social learning, rather than competitive self-evaluation, is the psychological pathway that translates external financial influence into sound financial behavior among MSME actors. Practically, this finding suggests that financial literacy interventions for MSMEs should be designed around mentorship and socialization-based learning to build financial self-efficacy, rather than relying on competitor-benchmarking approaches that this study finds ineffective in changing financial behavior.